Primary Group A Streptococcus Peritonitis in a Healthy Child: A Case Report - Alex Drinnan; James Naprawa; Sunghoon Kim; Karim Mansour (Clinical Practice and Cases in Emergency Medicine, 2026)
Introduction: Group A streptococcus (GAS, Streptococcus pyogenes) is commonly associated with pharyngitis and skin and soft tissue infections, but invasive infection can occur. Primary bacterial peritonitis due to GAS is rare, especially in healthy children without nephrotic syndrome or immunocompromise. Case Report: We present a 21-month-old previously healthy male with four days of fever, irritability, and refusal to walk. Examination revealed abdominal distention and peritonitis. Computed tomography showed ascites and a normal appendix. Diagnostic laparoscopy revealed copious purulent peritoneal fluid; both peritoneal fluid and blood cultures were positive for GAS. He was treated with ampicillin-sulbactam followed by oral amoxicillin-clavulanate with complete recovery. Conclusion: This case highlights a rare presentation of invasive GAS as primary peritonitis in a healthy child. Clinicians should consider this diagnosis when peritonitis is present but imaging does not confirm appendicitis. Early surgical evaluation and targeted antimicrobials are essential.